تقويم برنامج تعليم اللغة العربية بوصفها لغة ثانية في كلية التربيّة بالجامعة الإسلاميّة العالميّة ماليزيا من وجهة نظر الدارسين - أوما أوني، بدماصي أحمد (Kulliyah of Education, International Islamic University Malaysia, 2017)
This study aimed at identifying quality standards of teaching Arabic as a second language at the Faculty of Education, International Islamic University Malaysia. The study was descriptive analytical method based on using survey questionnaire for data collection. The samples of the study consisted of forty one (41) out of forty-three (43) male and female students who are in the second and third academic year 2014-2015 at the said college. The research instrument consisted of (69) items divided into four sections namely; quality standards of teaching Arabic language as a second language, quality standards of objectives of teaching Arabic as a second language, quality standards of the courses material for teaching Arabic as a second language and learners' attitude towards quality standards of learning Arabic as a second language. Thereafter, the researcher sorted out the answers and details in statistical package for social sciences version (18.0 SPSS ver. 18.0) for analysis. The researcher adopts simple descriptive statistical analysis Contained Frequency distributions such as the percentage and mean to answer the research questions.The results of the study shows that teaching and learning Arabic as a second language meets the needs of learners, aspirations of society and the requirements of the labor market. The results also show the course effectiveness of teaching Arabic language to non-native speakers in enabling the students acquire writing and communication skills in the Arabic language; know the literature and culture of the Arabic language native speakers. However, the nature of the program and learning environment (bilingual or trilingual environment) prevailing in the University hinders the achievement of the desired objective in it as a result of the fact that learners prefer using English than the Arabic language and that the local language is commonly used among all students which have negative effects on learners specializing in Arabic as a second language.